Optimized Hybrid Structures in Bridge Construction. Issue 12 (24th November 2021) - Kasuga, Akio
Abstract: Hybrid structures have two major objectives. One is to make concrete structures lighter by combining different technologies. And another is to make structural functions clearer by combining different materials. This report outlines two examples of these objectives. The example of the first objective to make structure lighter is light‐weight bridges. We have been building many types of hybrid bridges, for example, the corrugated steel web type, the hybrid truss type and the composite girder type. However, when steel members are used, maintenance is required throughout the lifetime of the structure. To solve these issues, a new type of hybrid bridge has recently been developed – the butterfly web bridge. This new structure combines conventional concrete with high‐strength fibre‐reinforced concrete. The web consists of precast panels shaped like a butterfly wing. These members are reinforced using only prestressing steel in the tension area and have a thickness of just 15 cm. The remaining concrete members are cast‐in‐place. As a result, this new type of bridge achieves a weight reduction of 15 to 20 % compared with a conventional concrete box girder construction. The example of the second objective to make structural functions clear is the hybrid stay cable anchorage system in the tower of cable‐stayed and extradosed bridges. Basically, the steel absorbs the tensile forces of the horizontal component of the stay cable and the concrete absorbs the compressive forces of the vertical component. The steel box anchorage system developed during the 2000s has evolved to make its cheaper to construct in the 2010s. We have undertaken many experiments in our laboratory to confirm the structural behaviour of these evolving systems. The evolution of stay cable anchorage systems is outlined in this article. Abstract: Optimierte Hybridstrukturen im Brückenbau Hybride Strukturen haben zwei Hauptziele. Zum einen soll die Betonstruktur durch die Kombination verschiedener Technologien leichter werden, zum anderen sollen die strukturellen Funktionen durch die Kombination verschiedener Materialien deutlicher werden. In diesem Bericht werden diese beiden Hauptziele anhand von Beispielen dargestellt. Das erste Beispiel sind Leichtbau‐Brücken. Es wurden viele Arten von Hybridbrücken gebaut, z. B. den Typ mit gewelltem Stahlsteg, den Hybrid‐Fachwerktyp und den Verbundträgertyp. Wenn jedoch Stahlträger verwendet werden, müssen diese während ihrer Lebensdauer gewartet werden. Um diese Probleme zu lösen, wurde kürzlich eine neue Art der Hybridbrücke entwickelt. Dabei handelt es sich um eine Kombination aus herkömmlichem Beton und hochfestem faserverstärktem Beton in einem neuen Bauwerk. Das Bauwerk ist eine Butterflystegbrücke (butterfly web bridge). Für den Steg werden vorgefertigte Platten in Form eines Schmetterlingsflügels aus neuen Materialien verwendet. Dieses Element wird nur durch Spannstahl im Zugbereich verstärkt und hat eine Dicke von nur 15 cm. Der Beton der übrigen Teile ist Ortbeton. Dadurch kann das Gewicht dieses neuen Brückentyps um 15 bis 20 % im Vergleich zu konventionellen Betonkastenträgern reduziert werden. Das zweite Beispiel ist das hybride Schrägseilverankerungssystem im Turm von Schrägseil‐ und Extradosed‐Brücken. Grundsätzlich wird die horizontale Komponente, d. h. die Zugkraft, der Schrägseile durch Stahl und die vertikale Komponente, d. h. die Druckkraft, durch Beton aufgenommen. Das System der Stahlkastenverankerung wurde in den 2000er‐Jahren weiterentwickelt, um seine Kosten in den 2010er‐Jahren zu senken. Um das strukturelle Verhalten dieser weiterentwickelten Systeme zu bestätigen, wurden zahlreiche Versuche in unserem Labor durchgeführt. Die Entwicklung des Schrägseilverankerungssystems wird hier dargestellt.